Preyssler Heteropoly Acids Encapsulated in a Silica Framework for an Efficient Preparation of Fluorinated Hexahydropyrimidine Derivatives under Solvent-Free Conditions - Sathicq, Ángel G.; Ruiz, Diego M.; Constantieux, Tierry; Rodriguez, Jean; Romanelli, Gustavo P. (Synlett, 2014)
A series of trifluoromethylated hexahydropyrimidines was synthesized using Preyssler heteropoly acid H14NaP5W29MoO110 encapsulated in a silica framework as the catalyst under solvent-free conditions. This synthesis requires short reaction times (1.5 h) and 80 °C under solvent-free conditions to obtain good to excellent yields of 18 hexahydropyrimidine derivatives. Preyssler catalyst embedded in the silica matrix, unlike the bulk or supported on silica, is insoluble in polar media such as acetone, ethanol, or methanol, which allows easy removal of the reaction products without affecting catalytic activity.
Keywords: fluorinated hexahydropyrimidines; trifluoromethyl derivatives; Preyssler heteropoly acid; encapsulated in a silica framework; solvent-free; multicomponent reactions